FRI0046 Methotrexate Dose Reduction During DAS28 Remission was a Significant Factor Associated with Early Deterioration in Patients with Rheumatoid Arthritis from the Iorra Cohort. (9th June 2015) - Shidara, K.; Inoue, E.; Tanaka, E.; Yamaguchi, R.; Shimizu, Y.; Hoshi, D.; Sugimoto, N.; Nakajima, A.; Momohara, S.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: Maintenance of remission is an important therapeutic goal in rheumatoid arthritis (RA). Several studies have proposed that RA patients maintaining remission could alter their current RA treatment strategy by reducing or withdrawing biological therapy 1)2) . However, few studies have investigated what factors lead to the loss of remission in a short period of time in RA patients who had previously sustained a remission state. Objectives: To investigate the risk factors for early deterioration after sustained DAS28 remission in RA patients in daily practice by using the large, observational, Institute Of Rheumatology, Rheumatoid Arthritis (IORRA) cohort, in which data were collected biannually. Methods: RA patients were selected for this study if they were not in DAS28 remission between October 2008 and October 2009 but subsequently achieved and sustained DAS28 remission at two consecutive data collections. These patients were observed to determine if DAS28 remission was maintained for 3 years. Cox regression analyses were conducted to examine risk factors for early deterioration within 3 years after sustained DAS28 remission at two consecutive data collections (1-year DAS28 remission). Results: A total of 841 patients with a sustained 1-year DAS28 remission state were analyzed. Females comprised 83% of the study population. The mean (SD) age and disease duration were 57.3 (13.0) years and 11.9 (8.8) years, respectively. The mean (SD) DAS28 and Japanese version of the Health Assessment Questionnaire (J-HAQ) score were 2.1 (0.4) and 0.4 (0.5), respectively. The mean (SD) methotrexate dosage and percentage of biologic use was 8.4 (3.3) mg/week and 18%, respectively. The proportions of the patients whose disease activity deteriorated within 1, 2 or 3 years after a sustained 1-year DAS28 remission state were 41.4%, 57.0% and 64.4%, respectively. Cox regression analyses confirmed that longer disease duration (p=0.045), higher DAS28 score during a 1-year DAS28 remission (p<0.0001), and decrease in methotrexate dose during the DAS28 remission state (p=0.03) were the significant factors associated with early deterioration from the DAS28 remission state. Conclusions: A decrease in the methotrexate dose during DAS28 remission was a significant factor associated with early deterioration in patients with RA in daily practice. Methotrexate dose reductions should be done prudently even in patients with sustained DAS28 remission. References: Smolen JS et al., Lancet. 2013;381:918-29. Tanaka Y et al., Clin Exp Rheumatol 2013;31:S22-7 Disclosure of Interest: K. Shidara: None declared, E. Inoue: None declared, E. Tanaka: None declared, R. Yamaguchi: None declared, Y. Shimizu: None declared, D. Hoshi: None declared, N. Sugimoto: None declared, A. Nakajima: None declared, S. Momohara Consultant for: AbbVie, Bristol-Myers-Squibb, Eisai, Mitsubishi-Tanabe, and Takeda, A. Taniguchi Grant/research support from: Takeda, Consultant for: AbbVie, Eisai, Mitsubishi-Tanabe, and Teijin, H. Yamanaka Grant/research support from: AbbVie, Asahikasei Pharma, Astellas, Bristol-Myers-Squibb, Chugai, Daiichi-Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi-Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taisho-Toyama, Takeda, Teijin Pharma, Consultant for: Teijin Pharma, Chugai, Astellas, Bristol-Meyers, AbbVie, Daiichi-Sankyo, Nihon-Kayaku, Mitsubishi-Tanabe, Pfizer, Takeda, UCB